Early life malnutrition and fluctuating asymmetry in the rat bony labyrinth. Issue 12 (1st March 2021) - Ward, Devin L.; Schroeder, Lauren; Pomeroy, Emma; Roy, Jocelyn E.; Buck, Laura T.; Stock, Jay T.; Martin‐Gronert, Malgorzata; Ozanne, Susan E.; Silcox, Mary T.; Viola, T. Bence
Abstract: Maternal malnutrition during gestation and lactation is known to have adverse effects on offspring. We evaluate the impact of maternal diet on offspring bony labyrinth morphology. The bony labyrinth develops early and is thought to be stable to protect vital sensory organs within. For these reasons, bony labyrinth morphology has been used extensively to assess locomotion, hearing function, and phylogeny in primates and numerous other taxa. While variation related to these parameters has been documented, there is still a component of intraspecific variation that is unexplained. Although the labyrinthine developmental window is small, it may provide the opportunity for developmental instability to produce corresponding shape differences, as measured by fluctuating asymmetry (FA). We hypothesized that (a) offspring with poor maternal diet would exhibit increased FA, but (b) no unilateral shape difference. To test these hypotheses, we used two groups of rats ( Rattus norvegicus ; Crl:WI[Han] strain), one control group and one group exposed to a isocaloric, protein‐restricted maternal diet during gestation and suckling. Individuals were sampled at weaning, sexual maturity, and old age. A Procrustes analysis of variance identified statistically significant FA in all diet‐age subgroups. No differences in level of FA were identified among the subgroups, rejecting our first hypothesis. A principal components analysis identified no unilateral shape differences, supporting our second hypothesis. These results indicate that bony labyrinth morphology is remarkably stable and likely protected from a poor maternal diet during development. In light of this result, other factors must be explored to explain intraspecific variation in labyrinthine shape.